Application of permeable materials for CBRN protective equipment - Zlate Veličković; Aleksandar Nikolić; Mirjana Kostić; Dalibor Jovanović; Željko Senić (Zaštita Materijala)
The new concept of chemical, biological, radiological and nuclear combat clothing offers the opportunity of substantial cost savings by eliminating the need for additional, CBRN over garments, whose high weight and poor breathability may cause a physiological overload of the soldier. These specific clothing made of filtrosorption material has been designed for modern soldier, increasing his efficiency and reducing total costs. Textile materials embedded in the suit have excellent physical and mechanical properties, air and moisture permeability after climatic treatment and practical usage. During testing of chemical protective over garment's physiologic suitability the ergometric indicators were determined.